2014
DOI: 10.2147/tcrm.s35075
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated lipodystrophy: a review from a Brazilian perspective

Abstract: The prognosis of human immunodeficiency virus (HIV)-infected individuals has dramatically improved worldwide since the introduction of highly antiretroviral therapy. Nevertheless, along with the decrease in mortality, several body modifications not initially related to HIV infection have been reported. Disorders in lipid and glucose metabolism, accompanied by body shape abnormalities and alterations in fat distribution, began to be described. A syndrome, named “HIV-associated lipodystrophy syndrome”, was coine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Combination antiretroviral medications (ARTs) improved the survival and quality of life of HIV infected patients, but they have many side effects. Lipodystrophy and metabolic abnormalities, among other adverse reactions may lead to cardiovascular problems [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination antiretroviral medications (ARTs) improved the survival and quality of life of HIV infected patients, but they have many side effects. Lipodystrophy and metabolic abnormalities, among other adverse reactions may lead to cardiovascular problems [15].…”
Section: Introductionmentioning
confidence: 99%
“…LD causes body changes which are usually associated with a decrease in self-esteem and leads to decreasing of adherence to ART and is associated to cardiovascular problems [1] This syndrome can also impact on quality of life, causes mental health disorders [10] and ultimately lead to treatment failure [1, 10]. Dual energy X-ray absorptiometry (DEXA) scan is a reliable method for definition of this syndrome [9].…”
Section: Introductionmentioning
confidence: 99%
“…HIV causes insulin resistance and dyslipidemia [ 11 ], and HCV is associated with intrahepatic elevation of tumor necrosis factor–α levels, insulin resistance, and liver disease [ 12 ]. Although initial studies associated the onset of diabetes in PLWHA to ART containing protease inhibitors (PIs) [ 13 , 14 ], which cause hyperglycemia by preventing the uptake and metabolism of glucose and lipids by adipocytes and hepatocytes [ 15 ], findings subsequently pointed toward the nucleoside reverse transcriptase inhibitors (NRTIs) and nonnucleoside reverse transcriptase inhibitors by virtues of their mitochondrial toxicity and apoptosis of adipocytes [ 9 , 16 ]. However, recent studies have suggested that traditional risk factors for diabetes such as age and body weight are the major predictors of the development of type 2 diabetes mellitus (T2DM), as opposed to medications [ 6 ].…”
mentioning
confidence: 99%
“…The development of combined antiretroviral therapy (ARVT), which rendered the important sustained suppression of viral replication, modified the clinical course of AIDS and its epidemic profile (1). The free and universal access to ARVT, established by the Brazilian government, caused a profound impact in the history of HIV infection, decreasing mortality and opportunistic infections, and had a consequent increase in the survival of carriers (2). According to the data from the Boletim Epidemiológico de 2014 (3), until October of that year, around 400 thousand people who live with HIV/AIDS (PVHA = PLWHA) had received ARVT for free from the Unified Health System (SUS) (4).…”
Section: Introductionmentioning
confidence: 99%